ANALISIS KAPASITAS DAN KINERJA LALU LINTAS DI JALAN H.R. RASUNA SAID JAKARTA - Edmund Surya Jaya; Najid Najid (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2021)
Some of the main roads in South Jakarta, one of which is Jalan H.R. Rasuna Said, which is always crowded with passing vehicles, both residents of Jakarta and Jabodetabek, traffic on Jalan HR Rasuna Said Jakarta often experiences congestion, one of the causes is the increase in the number of vehicles in the city and also traffic performance which is not matched by an increase in number. road users. The increase in the volume of traffic will cause a change in behavior towards traffic performance, based on the guidelines of MKJI 1997 (Manual of Indonesian Road Capacity) the value of road capacity is C = 6968 pcu/km with a free flow speed of Fv = 59,55 km/hour while the capacity Greenberg's selected model produces a capacity of C = 11384 pcu/km with a free flow speed of Sff = 49,72 km/hour while the condition of the passing vehicle exceeds the basic capacity based on MKJI 1997, namely the maximum volume of V = 10635 pcu/km and with a speed of S = 18,25 km/hour so that the research model that will be used as a reference for the next calculation is the Greenberg model. ABSTRAKBeberapa ruas jalan raya di Jakarta Selatan salah satunya adalah jalan H.R. Rasuna Said yang selalu dipadati dengan kendaraan yang melintas baik itu warga Jakarta maupun dari Jabodetabek, lalu lintas di Jalan H.R Rasuna Said Jakarta sering sekali mengalami kemacetan salah satu penyebabnya adalah peningkatan jumlah kendaraan di dalam kota dan juga kinerja lalu lintas yang tidak diimbangi oleh meningkatnya jumlah pengguna jalan. Peningkatan jumlah volume lalu lintas akan menyebabkan perubahan perilaku terhadap kinerja lalu lintas, berdasarkan pedoman MKJI 1997 (Manual Kapasitas Jalan Indonesia) nilai kapasitas ruas jalan sebesar C = 6968 smp/km dengan kecepatan arus bebas sebesar Fv = 59,55 km/jam sedangkan kapasitas model terpilih Greenberg menghasilkan kapasitas C = 11384 smp/km dengan kecepatan arus bebas Sff = 49,72 km/jam sedangkan kondisi kendaraan yang melintas melebihi kapasitas dasar bedasarkan MKJI 1997 yaitu volume maksimum sebesar V = 10635 smp/km dan dengan kecepatan S = 18,25 km/jam sehingga model penelitian yang akan digunakan sebagai acuan perhitungan selanjutnya adalah model Greenberg.